Preliminary observations on the reproductive biology of six species of Sri Lankan sea snakes (Elapidae: Hydrophiinae) - de Silva, A.; Ukuwela, K.D.B.; Sivaruban, A.; Sanders, K.L. (Deutsche Gesellschaft für Herpetologie und Terrarienkunde e.V. (DGHT), 2011)
We report on observations on the reproductive biology of viviparous sea snakes (Hydrophiinae) collected from marine fishing bycatches in Sri Lanka. Reproductive conditions were classified only in females by checking for the presence of eggs, embryos and vitellogenic follicles. A total of 33 specimens belonging to six species (Enhydrina schistosa, Hydrophis cyanocinctus, Hydrophis fasciatus, Hydrophis gracilis, Lapemis curtus and Thalassophina viperina) were represented by individuals in active reproductive condition. The total number of eggs and embryos in females ranged from 3 to 16; the lowest number of eggs was observed in T. viperina and the highest in E. schistosa. These findings are among the first to be recorded for some species of sea snakes in the South Asian region.
Keywords: Eggs; Gravid; Ovoviviparity; Reproduction; Sea snakes; Sri Lanka; Vitellogenic follicles